2018
DOI: 10.1177/0886260518789903
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Attitudes Toward Intimate Partner Violence Against Women: An Exploratory Study

Abstract: There is consistent evidence that attitudes are important in understanding how people react and behave toward victims and perpetrators of intimate partner violence against women. Researchers have typically measured these attitudes through self-reports. However, explicit measures are prone to socially desirable responding. The overall objective of our research is to provide multimethod measures of public attitudes (explicit and implicit) toward intimate partner violence against women. An opportunity sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
(111 reference statements)
1
16
0
Order By: Relevance
“…The Gender Violence Implicit Association Test (GV-IAT, Ferrer-Pérez et al, 2018 ; Sánchez-Prada et al, 2018 ) is a form of personalized IAT used as an implicit measure of attitudes toward IPVAW with two target categories, Gender Violence vs. Non-Gender Violence (the most distinctive feature of this personalized IAT) and two attribute categories, Good vs. Bad . Regarding the target category, Gender Violence vs. Non-Gender Violence, it is important to note that under Spanish law (Organic Act 1/2004, of 28 December, on Integrated Protection Measures against Gender Violence), IPVAW is known as gender violence (see Ferrer and Bosch, 2014 ), which is why GV-IAT uses gender violence to refer to IPVAW.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gender Violence Implicit Association Test (GV-IAT, Ferrer-Pérez et al, 2018 ; Sánchez-Prada et al, 2018 ) is a form of personalized IAT used as an implicit measure of attitudes toward IPVAW with two target categories, Gender Violence vs. Non-Gender Violence (the most distinctive feature of this personalized IAT) and two attribute categories, Good vs. Bad . Regarding the target category, Gender Violence vs. Non-Gender Violence, it is important to note that under Spanish law (Organic Act 1/2004, of 28 December, on Integrated Protection Measures against Gender Violence), IPVAW is known as gender violence (see Ferrer and Bosch, 2014 ), which is why GV-IAT uses gender violence to refer to IPVAW.…”
Section: Methodsmentioning
confidence: 99%
“…According to the literature review, the typical IAT procedure with feedback was used ( Greenwald et al, 1998 ; Nosek et al, 2007a , 2014 ; Sánchez-Prada et al, 2018 ). Participants completed the GV-IAT task in seven blocks ( Greenwald et al, 2003 ): The first block was the initial target concept discrimination task, which included 24 practice trials, where participants sorted non-gender-violence (i.e., tolerate, support, respect, empathize, cooperate, and collaborate) and gender-violence (i.e., torture, infringe, humiliate, hit, force, and attack) behaviors into the categories “non-gender-violence” and “gender-violence” using the “s” key (left) and the “l” key (right).…”
Section: Methodsmentioning
confidence: 99%
“…The Gender Violence Implicit Association Test (GV-IAT [64][65][66]) is a form of personalized IAT used as an implicit measure of attitudes towards IPVAW with two target categories-Gender Violence vs. Non-Gender Violence-and two attribute categories-Good vs. Bad. Related to the target category, it is important to note that, under Spanish law [67], IPVAW is known as gender violence (see [25]), which is why GV-IAT uses the term "Gender Violence" to refer to IPVAW.…”
Section: Participantsmentioning
confidence: 99%
“…The IAT effect (D-scores) is calculated using the difference between incompatible-compatible critical phase latency-based responses [54,64]. The typical IAT procedure with feedback was used [64,66], and the participants completed the GV-IAT task in seven blocks, of which three were considered practice trials (B1-B2 including 24 trials and B5 including 48 trials) and four as critical blocks (B3-B6 including 24 trials in the compatible phase and B4-B7 including 48 trials in the incompatible phase) [54]. Additionally, the first trials of each critical block were considered "practice trials" and only the next trials of each block were computed in the D score (in the end, 20 trials were computed in B3-B6 and 40 trials in B4-B7).…”
Section: Participantsmentioning
confidence: 99%
“…Nonetheless, this study is one of the first posing the association between attitudes towards violence and these mental health issues. In addition, previous studies have established the relation between attitudes toward violence and explicit IPV [ 43 ]. With regards to the mediation analysis, the results of the SEM revealed that depression mediated the relationship between attitudes towards violence and scores on the M-CTS.…”
Section: Discussionmentioning
confidence: 99%